Morphological Awareness in L2 Chinese Reading Comprehension: Testing of Mediating Routes - Zhang, Haomin; Zhang, Xing; Li, Mengjie; Zhang, Yiming (Frontiers in Psychology, 2021)
The present study aims to examine the mediated and unmediated role of morphological awareness in second language (L2) Chinese reading comprehension. Adult L2 Chinese learners (N=447) participated in the study and completed two morphological awareness tasks (segmentation and discrimination), two vocabulary knowledge tasks (character knowledge and word-meaning knowledge), one lexical inference task and one reading comprehension task. By testing alternative path models, the study identified the preferred model assuming the covariates of morphological awareness and vocabulary knowledge. Both morphological awareness and vocabulary knowledge jointly contributed to L2 Chinese reading comprehension through lexical inference. The visually presented task modality of morphological awareness induced the activation of both morphological and orthographic information in print. The result suggests that morphological awareness (in the form of graphomorphological knowledge) and vocabulary knowledge seem to be two parallel components under the same construct predicting Chinese reading comprehension. More important, the study underscores the intermediary effect of lexical inference in associating morphological awareness and reading comprehension in L2 Chinese learners.